O2 plasma and cation tuned nickel phosphide nanosheets for highly efficient overall water splitting - Dinh, Khang Ngoc (2020)
Here we present a novel combined-strategy of cation tuning and surface engineering for the fabrication of highly active, earth-abundant, and robust two-dimensional Ni2P electrocatalyst. The nanosheets have lateral sizes of few hundred nm with thicknesses of ~6 nm. Our theoretical calculations suggest the effectiveness of vanadium doping and oxygen plasma, which do not only enhance the density-of-state at Fermi level, but also make the Ni sites more susceptible to OH− adsorption. The oxygen plasma treatment can increase the wettability of the catalyst toward KOH solution, improving the contact angle from 44.95° to 16.8° and also induce a higher BET surface area; hence, more active sites and lower charge transfer resistance are obtained. As a result, the catalyst requires small overpotentials of 257 and 108 mV to drive ±10 mA cm−2 alongside with modest Tafel slope of 43.5 and 72.3 mV dec−1 for oxygen evolution reaction and hydrogen evolution reaction in 1.0 M KOH solution, respectively. When employed for overall water splitting, the catalyst demonstrates a low voltage of 1.56 V to achieve 10 mA cm−2 with good stability and durability, outperforming the state-of-the-art IrO2 || Pt/C which needs 1.69 V. This work opens a new approach to engineer low-cost monometallic phosphides for highly efficient water splitting.